(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article analyzes world trends and foreign experience in creating a new paradigm in the development of information and library education in the digital era. The necessity of using innovative technologies in bachelor's degree in teaching information and library disciplines, the purpose, teaching methods and results of research are discussed. What, in turn, needs to be done and what will help to train highly qualified specialists for information and library specialists of the republic.